Giving Context to the Physician Competency Reference Set: Adapting to the Needs of Diverse Populations. (July 2016) - Eckstrand, Kristen L.; Potter, Jennifer; Bayer, Carey Roth; Englander, Robert
Abstract : Delineating the requisite competencies of a 21st-century physician is the first step in the paradigm shift to competency-based medical education. Over the past two decades, more than 150 lists of competencies have emerged. In a synthesis of these lists, the Physician Competency Reference Set (PCRS) provided a unifying framework of competencies that define the general physician. The PCRS is not context or population specific; however, competently caring for certain underrepresented populations or specific medical conditions can require more specific context. Previously developed competency lists describing care for these populations have been disconnected from an overarching competency framework, limiting their uptake. To address this gap, the Association of American Medical Colleges Advisory Committee on Sexual Orientation, Gender Identity, and Sex Development adapted the PCRS by adding context- and content-specific qualifying statements to existing PCRS competencies to better meet the needs of diverse patient populations. This Article describes the committee's process in developing these qualifiers of competence. To facilitate widespread adoption of the contextualized competencies in U.S. medical schools, the committee used an established competency framework to develop qualifiers of competence to improve the health of individuals who are lesbian, gay, bisexual, transgender; gender nonconforming; or born with differences in sexual development. This process can be applied to other underrepresented populations or medical conditions, ensuring that relevant topics are included in medical education and, ultimately, health care outcomes are improved for all patients inclusive of diversity, background, and ability.